HUBUNGAN ANTARA PERILAKU MAKAN DENGAN STATUS GIZI PADA REMAJA PUTRI - Pujiati ' '; Arneliwati ' '; Siti ' Rahmalia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Perfect body was a dream of all adolescents girl so many girl done a strict diet with bad eating behaviour. Wrong way that they used can decrease their nutritional status. Adolescent eating behaviour who wasn’t think about nutritional made adolescents more likely to eat fast food, so will changed adolescent eating behaviour became good or bad behaviour. The aim of this study was to know correlate between adolescent girl eating behaviour and nutritional status in RW 5 Kelurahan Cinta Raja Kecamatan Sail, Pekanbaru City. 62 samples with purposive sampling technique. Univariate and bivariate analysis was conducted to analize the data. Data was analyzed using frequency distribution table and chi square test. Statistic showed p value (0,331). which means there is correlation between adolescent girl eating behaviour and nutritional status and was suggested for the family who had adolescent girl to control their eating behaviour and for the healthcare provider was suggested to increased health education about eating behaviour. Keywords: adolescent girl, eating behaviour, nutritional status